Posture constructions: between depictives and resultatives - Riaubienė, Benita (Kalbotyra, 2016)
The paper examines Lithuanian posture constructions such as stovi stačias ‘stands uprightʼ which have been briefly discussed in Holvoet (2008). However, a more exhaustive examination has not been carried out yet. The discussion is based on 1002 examples fromThe Corpus of the Contemporary Lithuanian Language. Some of the secondary predicates occurring in posture constructions exhibit semantic features of either resultatives or depictives, while the others cannot be clearly judged as resultatives or depictives since they show both kinds of features. The encoding of the secondary predicates also oscillates between the depictive and the resultative marking. Thus the purpose of the paper is to establish the factors which determine different semantic interpretations and different formal marking of the construction. The author follows Holvoet (2008) in assuming that the semantic structure of the constructions depends on the semantic features of the verb. It is proposed that the lexical aspect and the lexical meaning of the verb determine a resultative, a depictive or a “neutralized” (“intermediate”) interpretation of the construction. As the data show, the secondary predicate is usually encoded by an adjective (depictive-like marking), however, sometimes it is expressed by an adverb (resultative-like marking) as well. It is assumed that the choice between the adjective and the adverb is determined by the lexical features of the secondary predicate rather than of the verb. Some of the posture notions seem to be more oriented towards the participant of an event and thus opt to be expressed by an adjective, while others are more oriented towards the event and therefore are encoded by an adverb. It is hypothesized that the reason for the oscillating marking lies in the constructions with a neutralized meaning. The cases which are ambiguous between the depictive and the resultative meaning constitute a precondition for establishing the double marking. This twofold marking is then extended to the constructions which carry clearly the depictive or the resultative meaning.